التطرف المنظور القراني دراسة موضوعية - Byan Jamal Al-Waqfy; Mallak Damen Abood (Penerbit USIM, 2025)
International Conference of Quran as Foundation of Civilization (SWAT 2025) : Maqasid al-Quran and the Madani Vision: A Guiding Light for Regional Serenity and Global Unity Organized by : Faculty of Quranic and Sunnah Studies, in collaboration with Nasyrul Quran and Daffodil International University, Bangladesh. Date:12-13 November 2025